2021
DOI: 10.1039/d1sc02352g
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 2 + 1] Cycloaddition of N-tosylhydrazones, tert-butyl nitrite and alkenes: a general and practical access to isoxazolines

Abstract: N-Tosylhydrazones have proven to be versatile synthons over the past several decades. However, to our knowledge, the construction of isoxazolines based on N-tosylhydrazones has not been examined. Herein, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…In the following edge article from 2021, a new type of CuCl 2 -catalyzed [2 + 2 + 1] cycloaddition leading to isoxazolines was presented— Scheme 283 [ 314 ]. Significantly, the RCNOs are not involved in the reaction method.…”
Section: Methods Of 2-isoxazolines Synthesis Other Than Dipolar Cyclo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the following edge article from 2021, a new type of CuCl 2 -catalyzed [2 + 2 + 1] cycloaddition leading to isoxazolines was presented— Scheme 283 [ 314 ]. Significantly, the RCNOs are not involved in the reaction method.…”
Section: Methods Of 2-isoxazolines Synthesis Other Than Dipolar Cyclo...mentioning
confidence: 99%
“… Syntheses of 3,5-disubstituted isoxazolines from in situ-generated nitronates [ 314 ]. Examples of biologically important compounds.…”
Section: Figures and Schemesmentioning
confidence: 99%
“… Strategy for the synthesis of skeleton-fused isoxazole/isoxazoline. (HAT: Hydrogen Atom Transfer) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. …”
Section: Figures and Schemesmentioning
confidence: 99%
“…Wan, X.-B. et al reported the graceful cycloaddition reactions for the synthesis of isoxazoles from diazo compounds or N -tosylhydrazones with alkenes or β -keto esters activated by tert -butyl nitrite [ 29 , 30 , 31 ]. These approaches are robust and can deliver fully substituted isoxazoles.…”
Section: Introductionmentioning
confidence: 99%
“…This feature of isoxazole makes it a key pharmaceutical fragment in many drugs [ 47 , 48 , 49 ]. In recent years, tert -butyl nitrite (TBN) has acted as a metal-free radical initiator and source of N-O [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], which has attracted extensive attention in the construction of isoxazoles [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Despite these excellent methods, there are few reports on the construction of skeletal cores containing isoxazole and tricyclic quinazoline alkaloids or their derivatives.…”
Section: Introductionmentioning
confidence: 99%